On Second Gourava Invariant for q-Apex Trees - Ying Wang; Salma Kanwal; Maria Liaqat; Adnan Aslam; Uzma Bashir (Journal of Chemistry)
Let G be a simple connected graph. The second Gourava index of graph G is defined as GO2G=∑θϑ∈EGdθ+dϑdθdϑ where dθ denotes the degree of vertex θ. If removal of a vertex of G forms a tree, then G is called an apex tree. Let L⊂VG with ∣L∣=q. If removal of L from VG forms a tree and any other subset of VG whose cardinality is less than ∣L∣ does not form a tree, then G is known as q-apex tree. In this paper, we have calculated upper bound for 2nd Gourava index with respect to q-apex trees.